Late viral interference induced by transdominant Gag of an endogenous retrovirus - Mura, Manuela (National Academy of Sciences, 2004)
The sheep genome harbors ≈20 copies of endogenous retroviruses (enJSRVs) closely related to the exogenous and oncogenic Jaagsiekte sheep retrovirus (JSRV). One of the enJSRV loci, enJS56A1, has a defect for viral exit. We report a previously uncharacterized mechanism of retroviral interference. The defect possessed by enJS56A1 is determined by its Gag protein and is transdominant over the exogenous JSRV. By electron microscopy, cells transfected by enJS56A1, with or without JSRV, show agglomerates of tightly packed intracellular particles most abundant in the perinuclear area. The defect in exit and ability to interfere with JSRV exit could be largely attributed to the presence of tryptophan, rather than arginine, at position 21 of enJS56A1 Gag; C98 and V102 also contribute to these properties. We found that enJS56A1 or similar loci containing W21, C98, and V102 are expressed in sheep endometrium. enJS56A1 is a previously unrecognized example of a naturally occurring endogenous retrovirus expressing a dominant negative Gag acting at a late step of the viral replication cycle. Understanding the late blockade exerted by enJS56A1 could unravel fundamental aspects of retroviral biology and help to devise new antiretroviral strategies.